Kegiatan sebagai Pembicara dalam Seminar Merajut Nusantara “Kemampuan Digital yang Dicari Saat ini” - TIUAJ, yanto (Jurnal Pengabdian Masyarakat Charitas, 2024)
This community service activity aimed to provide insight and knowledge regarding digital skills needed in the future for the participants. There were three speakers who presented various topics related to digital skills in demand today. In the digital era, it requires people who have adequate relevant digital skills. Based on presentation, 7 digital skills in demand today are social media skills, the ability to optimize SEM (Search Engine Marketing), data analytics, content marketing, social selling, mobile marketing skills and the ability to create or modify video content. In this digital era, creativity, innovation and adaptability are needed so that individuals are able to compete and to be successful.